The role of the Zakat Fund in financing entrepreneurial projects to achieve development (Journal of Accounting and Financial Studies ( JAFS ), 2021)
This study aims to identify how the Zakat Fund contributes to financing entrepreneurial projects; and the role that these projects play in achieving economic and social development, despite the importance that contracting projects have in most countries as the main engine of growth; however, they still face many challenges that In the forefront of which is the challenge of obtaining financing; in this regard, it is possible to resort to the use of Zakat funds in the Islamic economy as it is a funding source that is closely proportional to the characteristics and goals of entrepreneurial projects in achieving development;       As this study examined the experience of Sudan in using zakat funds to finance entrepreneurial pro   jects for the benefit of the poor and needy in order to improve their conditions; and it concluded that the use of zakat funds can be an appropriate source of funding to support and create entrepreneurial projects that contribute to reducing unemployment and fighting poverty and access To achieve economic and social development.